Hydroeconomic Analysis to Guide Climate Adaptation Plans - Ward, Frank A. (Frontiers in Water, 2021)
Title: Hydroeconomic Analysis to Guide Climate Adaptation Plans Successful climate adaptation needs to sustain food, water, and energy security in the face of elevated carbon emissions. Hydroeconomic analysis (HEA) offers considerable potential to inform climate adaptation plans where water is an important element of economic activity. This paper’s contribution is to identify how HEA can inform climate adaptation plans by minimizing economic costs of responding to climate induced changes in water supplies. It describes what HEA is, why it is important, how researchers implement it, who has made significant contributions, and places where it has informed policy debates. It also describes future directions for the use of HEA to guide climate adaptation.